(untitled) (Research, Society and Development, 2021)
According to data released by the American Dental Association (ADA), more than 5 million teeth are avulsed each year, with sports being responsible for about 39% of these cases. According to the North American Association of Sports Dentistry, the use of mouthguards during sports practices reduces the risk of dental organ loss by up to 80% and the chance of tooth fractures by 90%. The aim of this study was to identify the level of knowledge about the use of mouthguards for sports among senior dentistry students in an institution in the southwest of Bahia. A questionnaire with 8 questions was applied to students from the 9th and 10th semester of the Dentistry course at an institution in the southwest of Bahia. The results suggest that although most of the academics interviewed have already heard about sports mouthguards, they do not distinguish between their various types, the possible injuries that can be avoided with their use, and the sports that require the use of this protective device. It is concluded that the level of knowledge about sports mouthguards among academics proved to be low.